A Functional Approach to the Assessment of Non-Suicidal Self-Injury on YouTube. (9th September 2022) - Steele, Morgan A.; Power, Jenelle; Smith, Hayden P.
Abstract: This research explores representations of non-suicidal self-injury (NSSI) on social media. The current study aims to examine the applicability of a functional model of NSSI to videos posted on YouTube by analyzing the 100 most viewed YouTube videos relating to NSSI at a point in time in 2018. Motivations for continued engagement in NSSI were examined for each content creator who posted one of the top 100 most viewed videos relating to NSSI. Categorizations of a content creator's motivation were based on Nock and Prinstein (2004 ) four-function model (FFM) of NSSI, in which the motivations, or functions, of NSSI are categorized by two dichotomous factors: (a) positive (i.e., involves the addition of a favorable stimulus) or negative (i.e., involves the removal of an aversive stimulus) and (b) automatic (i.e., intrapersonal) or social (i.e., interpersonal). Uploaders most endorsed automatic negative reinforcement (50%), followed by automatic positive (26%), social positive (3%), and social negative (3%). Considering the growing number of children and adolescents with near constant access to internet and social media, there may be implications for further development of safety measures for social media platforms.ï»¿ The results of this study may be valuable for parents, health care professionals, and educators, who should be aware of available social media content relating to NSSI and consider implementing additional media-literacy and media-safety education in school curriculums and programming for children and adolescents. Furthermore, health care professional should be aware that misconceptions of NSSI may have an impact on patients' willingness to seek treatment, or the attitude with which treatment is sought.